Sosialisasi Senam Di Desa Taba Air Pauh - Efran, Efran; Sumantri, Ajis; Perdima, Feby Elra; Martiani, Martiani (Universitas Dehasen Bengkulu, 2024)
Gymnastics is not only a form of physical activity, but also includes a social dimension that can have a positive impact on individuals and society. Gymnastics socialization is an approach that embraces social interaction and collective participation in gymnastics activities, with the aim of improving physical and mental well-being, building healthy communities and preserving a culture of exercise. This article details the concept and benefits of gymnastics socialization and identifies factors that influence its successful implementation. With a focus on social integration and gymnastics activities, these efforts bring positive impacts in shaping interpersonal skills, improving mental and physical health, and strengthening social ties within communities. Awareness of the importance of gymnastics socialization is expected to stimulate increased community participation in sports activities that support general well-being.